Subjective Well-Being Among Teenager in Banda Aceh - Fitria, Ida; Hafiza, Sarah; Rasyidin, Ulfah (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
This study aims to determine the subjective well-being of adolescents in Banda Aceh. Adolescent well-being was measured by subjective well-being scales, which comprised with cognitive and affective aspects. A quantitative descriptive analysis approach was used in this study. The participants were 293 teenagers from various schools and universities that spread across Banda Aceh, both public and private. The data collection instruments used were the SWLS and SPANE scales. Results of this study indicate that, life satisfaction of adolescents in Banda Aceh majority was categorized in